Conducting standardized tests for students applying for admission to Faculties of Physical Education and Sports Sciences through a special electronic system - AL-NUAIMI, SAWSANJADDOA KADHIM (International Journal of Psychosocial Rehabilitation, 2020)
Workers on the subject of tests for admission in Physical Education & Sport Sciences College for the beginning of each academic year to great efforts in the process of testing as well as the steady increase in the number of students competing for seats to study for a degree in physical education jurisdiction, there are several tests to students, and standard grades are calculated for each test in conformity with traditional manual calculation methods, and then extract the desired number for admission, this our results in many problems, through difficult to demonstrate results with accuracy and speed, errors and omissions contained With the increase in the numbers of applicants, in addition to discrimination or preference among students at the expense of others.